Toxicity of the nicosulfuron herbicide on rice (Oryza sativa L.). - Esqueda, Valentín A. (2006)
The toxic effects of the herbicide nicosulfuron to rice cv. Milagro Filipino Depurado were determined under greenhouse conditions. Nicosulfuron at 40 and 80 g/ha, the mixture of nicosulfuron + 2,4-D (40 + 480 g/ha) and a nonherbicide treatment were evaluated. Herbicide treatments were applied to plants 3, 10, 17 y 24 days after emergence (DAE). Toxicity was evaluated seven days after application (DAA) and plant height was measured at seven, 15 and 30 DAA; the plant’s dry matter was also quantified at 30 DAA. The highest toxicity was observed in plants treated at three and 10 DAE with nicosulfuron at 80 g/ha and the mixture of nicosulfuron + 2,4-D. The height of rice plants applied with any of the herbicide treatments was significantly lower than that of the non-treated plants at seven and 15 DAA. The nontreatedplants were still  significantly taller than the treated plants at 30 DAA, except forthose treated at three DAE with 40 g nicosulfuron or with the mixture nicosulfuron + 2,4-D, at 10 DAE. Plants applied with 40 g nicosulfuron at 10 DAE or later had dry matter productions statistically similar to that of non-treated plants, while plants treated with 80 g nicosulfuron produced the lowest dry matter.